A COLLABORATION OF FOUR PILLARS IN COORDINATING PUBLIC PEACE AND ORDER IN KRAKSAAN WETAN SUBDISTRICT - Mistahul Munir; Ernani Hadiyati; Rini Astuti; Yosar Haritsar (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2026)
Abstract This study aims to analyze the forms of coordination, the urgency of coordination, the obstacles encountered, and the optimization efforts made by the village government, the Civil Service Police Unit, the police apparatus, and the community in maintaining public order and tranquility in Kraksaan Wetan Village, Probolinggo Regency. The research employs a descriptive qualitative approach with data collection techniques through in-depth interviews, participatory observation, documentation studies, and focus group discussions. The findings reveal that coordination takes place through vertical and horizontal relationships, routine and incidental meetings, community involvement through neighborhood forums and Community Protection Units, as well as the use of communication technology. This coordination is important for improving supervision effectiveness, reducing overlapping duties, accelerating the handling of social problems, and increasing community participation. The obstacles encountered include limitations in human resources and facilities, differences in perception among personnel, less than optimal community participation, as well as bureaucratic and regulatory hurdles. Optimization efforts are carried out through strengthening regular communication, improving the capacity of apparatus and Community Protection Units, developing information technology, policy advocacy, and cross-sector synergy. Keywords: coordination; public_order_and_tranquility; community_security; community_participation; village